Hydrochemical Characteristics and Formation of the Madeng Hot Spring in Yunnan, China. (2nd July 2018) - Zhenhua, Ren; Xun, Zhou; Miaolin, Yang; Xiaocui, Wang; Yuhui, Zheng; Xiaolu, Li; Ye, Shen
Abstract : The Madeng hot spring emerges in the central river valley in the northeastern Lanping Basin in Jianchuan county of Yunnan Province in China. Quaternary sand and gravel occur in the valley which is underlain by the red beds consisting of sandstone and mudstone. The temperature of the hot spring is 42.1°C. The spring water has a pH value of 6.41, TDS of 3.98 g/L, F contents of 3.08 mg/L, and H2 SiO3 of 35.6 mg/L. The hot water is of SO4 Cl-NaCa type. There is a slight hydrogen sulfide odor in the spring water. Stable hydrogen and oxygen isotopes indicate that the hot water is of meteoric origin. It is estimated that the elevation of the recharge area of the hot spring is approximately 3800 m, the age of the hot water is some 140 years, the temperature of the geothermal reservoir is 75°C–80°C, the mixture ratio of cold water is approximately 80%, and the circulation depth of the thermal groundwater is 1870 m. After receiving recharge from infiltration of precipitation in the mountainous recharge areas, the groundwater undergoes a deep circulation, obtains heat from the heat flow, flows upward along the fractured zone, and emerges as an upflow spring through the Quaternary sand and gravel in the central low-lying river valley.